The importance of repulsive potential barriers for the dispersion of graphene using surfactants - COLEMAN, JONATHAN; LOTYA, MUSTAFA; SMITH , RONAN JAMES (My University, 2010)
We have dispersed graphene in water, stabilized by a range of 12 ionic and non-ionic surfactants. In all cases, the degree of exfoliation, as characterized by flake length and thickness, was similar. The dispersed flakes were typically 750 nm long and, on average, four layers thick. However, the dispersed concentration varied from solvent to solvent. For the ionic surfactants, the concentration scaled with the square of the zeta potential of the surfactant-coated flakes. This suggests that the concentration is proportional to the magnitude of the electrostatic potential barrier, which stabilizes surfactant-coated flakes against aggregation. For the non-ionic surfactants, the dispersed graphene concentration scaled linearly with the magnitude of the steric potential barrier stabilizing the flakes. However, the data suggested that other contributions are also important.
PUBLISHED
Keywords: Fluids and plasma physics; Physical chemistry; Polymer science; graphene; Nanoscience & Materials